Numerical algortihms for solving two-phase flows based on relaxation Baer-Nunziato model - Alekseev, Mikhail V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2023)
The paper considers the issues of numerical simulation of two-phase flows in the Eulerian model of the Baer-Nunziato model. The description of the mathematic model, the numerical algorithm for solving the problem based on discontinuous Galerkin method are formulated. A description of the developed software package is provided with demonstration the possibility of its application for solving problems in actual grid sizes.